Management of economic and environmental sustainability in international political economy perspective. Issue 1 (October 2020) - Maszudi, E; Khaddapi, M; Kusdarianto, I; Hamid, R S; Muhammad; Jusni
Abstract: In this study, the author focused on the management material of environmental, economic sustainability from the perspective of the international political economy. The first study is the concept of management, environmental economics in the view of the international political economy in addressing development, which often creates economic disparity, environmental damage at the international, regional, and local levels. The method used is the study of literature.